THE TRADING HOUSE OF THE YAUSHEV BROTHERS IN TURKESTAN REGION AND THEIR CAPITAL IN THE REGULATORY SYSTEM - Parvina Ismoilova (Bright Mind Publishing, 2025)
The article shows that the trading house of the Yaushev brothers played an important role in the cotton economy of the Turkestan region, operating within the regulatory framework of the Russian Empire. According to the sources, their enterprise, founded in 1887, was engaged in the purchase, processing and sale of cotton, while maintaining financial independence from the dominant Russian banking institutions. While Moscow banks controlled 80-90 per cent of the financing of the region's cotton industry, the Yaushevs relied on their own capital and regional networks, using their Turkic-Tatar identity to strengthen economic ties with local producers. Their involvement went beyond the cotton trade to include agriculture and livestock, providing greater self-sufficiency in a system dominated by monoculture.
Keywords: Cotton, Turkestan, the Yaushevs, price, Azov-Don Commercial Bank, rubles, Partnership.